Dinámica de crecimiento de las especies forestales del bosque nublado en la reserva natural Tapichalaca, Palanda Zamora Chinchipe - Ney Brayan, Quezada Cabrera (2019)
Cloud forests are recognized as ecosystems that require special attention, due to their importance as a source and provider of water resources (FAO, 1996), they are also a priority for the conservation of biodiversity in the world. For this reason, this research is being carried out as a follow-up to the thesis project executed by Lozano and Yaguana (2009) that aims to contribute to the knowledge of the forest dynamics of the plant species of the cloud forest of the Tapichalaca Natural Reserve of the province of Zamora Chinchipe. To meet this objective, a permanent plot of 1 ha (100 m x 100 m) was monitored, divided into 25 subplots of 400 m2 (20 m x 20 m), within each subplot all individuals ≥ 10 cm of DAP were identified, they marked with red paint at 1.30 m above ground level and a new forest inventory was carried out. With the base information, ecological, dasometric parameters and forest growth dynamics in terms of birth rate, recruitment and Annual Average Increase (IMA) were evaluated. The inventory recorded 400 individuals belonging to 80 species, 29 families and 52 genera, with a baseline area of 25.99 m2/ha and a total volume of 248.15 m3/ha. The most abundant family was Rubiaceae and the most abundant genus Miconia and Guarea with 25 ind/ha. The most ecologically important species was Ficus insipida followed by Nectandra laurel and Guarea kunthiana. The diametric distribution shows an inverted J typical of non-intervened tropical forests or with good population dynamics. As for the growth dynamics, the mortality of the woody component of the cloud forest of the RNT, in the span of 10 years presents a total of 63 dead individuals corresponding to 1.95 %. However, in recruitment 118 individuals were registered, corresponding to a value of 3.42 %; with an average growth in diameter of 0.0303 ± 0.0144 and an annual periodic increase of 0.0030 m/ha/year, where the species with the highest average diameter growth is Guarea pterorhachis with a value of 0.005 ± 0.0248 m/ha (0.0055 m/ha/year), while Ficus insipida has the highest value in basal area and volume. The cloud forest has a volume of 248.1475 m3/ha, with gross forest growth with an income of 56.67 m3/ha. This monitoring allows to conclude that the cloud forest of Tapichalaca is very diverse and that within ten years the functional processes related to the development of the forest mass have not been disturbed but rather in a process of recovery of the same.